Spontaneous and Naloxone-Precipitated Withdrawal Behaviors From Chronic Opiates are Accompanied by Changes in N-Oleoylglycine and N-Oleoylalanine Levels in the Brain and Ameliorated by Treatment With These Mediators - Ayoub, Samantha M.; Piscitelli, Fabiana; Silvestri, Cristoforo; Limebeer, Cheryl L.; Rock, Erin M.; Smoum, Reem; Farag, Mathew; de Almeida, Hannah; Sullivan, Megan T.; Lacroix, Sébastien; Boubertakh, Besma; Nallabelli, Nayudu; et al. (Frontiers in Pharmacology, 2021)
Rationale: The endocannabinoidome mediators, N-Oleoylglycine (OlGly) and N-Oleoylalanine (OlAla), have been shown to interfere with acute naloxone-precipitated morphine withdrawal affective and somatic responses. Objectives: To determine the role and mechanism of action of OlGly and OlAla also in withdrawal responses from chronic exposure to opiates in male Sprague-Dawley rats. Methods: Opiate withdrawal was produced: 1) spontaneously 24 hr following chronic exposure to escalating doses of morphine over 14 days (Experiments 1 and 2) and steady-state exposure to heroin by minipumps for 12 days (Experiment 3), 2) by naloxone injection during steady-state heroin exposure (Experiment 4), 3) by naloxone injection during operant heroin self-administration (Experiment 5). Results: In Experiment 1, spontaneous morphine withdrawal produced somatic withdrawal reactions. The behavioral withdrawal reactions were accompanied by suppressed endogenous levels of OlGly in the nucleus accumbens, amygdala and prefrontal cortex, N-Arachidonyl glycerol and OlAla in the amygdala, 2-arachidonoylglycerol in the nucleus accumbens, amygdala and interoceptive insular cortex, and by changes in colonic microbiota composition. In Experiment 2, treatment with OlAla, but not OlGly, interfered with spontaneous morphine withdrawal responses. In Experiment 3, OlAla interfered with spontaneous steady-state heroin withdrawal responses at both 5 and 20 mg/kg; OlGly only interfered with withdrawal at the higher dose of 20 mg/kg. Experiment 4 demonstrated that naloxone-precipitated heroin withdrawal from steady-state exposure to heroin (7 mg/kg/day for 12 days) is accompanied by tissue-specific changes in brain or gut endocannabinoidome mediator, including OlGly and OlAla, levels and colonic microbiota composition, and that OlAla (5 mg/kg) interfered with behavioural withdrawal reactions, while also reversing some of the changes in brain and gut endocannabinoidome and gut microbiota induced by naloxone. Experiment 5 demonstrated that although OlAla (5 mg/kg) did not interfere with operant heroin self-administration on its own, it did interfere with naloxone-precipitated elevation of heroin self-administration behavior. Conclusions: These results suggest that OlAla and OlGly are two endogenous mediators whose brain concentrations respond to chronic opiate treatment and withdrawal concomitantly with changes in colon microbiota composition, and that OlAla may be more effective than OlGly in suppressing chronic opiate withdrawal responses.